THE DIFFERENCES LEVEL OF INTERLEUKIN-22 BETWEEN POSITIVE AND NEGATIVE HELICOBACTER PYLORI GASTRITIS - P Nancy, AS Gontar & L Dharma (International Journal of Research Science and Management, 2020)
Introduction: Helicobacter pylori (H. pylori) is the most common cause of chronic gastritis worldwide. H. pylori infection will cause an increase in mononuclear (MN) and polymorphonuclear (PMN) cell infiltration and will increase the production of proinflammatory cytokines namely Interleukin-22. This study aimsto determine differences of serum Interleukin-22 level between positive and negative Helicobacter pylori (H. pylori) patient groups. Methods: This study was a cross-sectional study. Inclusion criteria are stated as followings: male or female aged ≥ 18 years old at Adam Malik General Hospital & Permata Bunda Hospital Medan started from May to August 2019, patients diagnosed with gastritis by an endoscopic, signed the patient consent forms, none of the patients had received antibiotics, a bismuth compound, H2 antagonists, proton pump inhibitors within the last four weeks before endoscopy. Patients with evidence of malignancy, immunosuppression, metabolic disorders, gastrointestinal haemorrhage, had a history of gastric surgery were excluded.H. pylori was examined by Campylobacter Like Organism test (CLO).Univariate and bivariate analysis (mann-whitney test), were done using SPSS version-22. Results: Of the 60 subjects, they are divided into 2 groups; 32 subjects in the negative H. pylori group and 28 subjects in the positive H. pylori group. The median serum IL-22 level in positive H. pylori was 55,5 (23 – 104) pg / ml and negative H. pylori was 19 (16-23) pg / ml. Conclusion: There were statistically significant (p<0,001) differences in serum IL-22 levels between positive and negative H. pylori patient groups.